Improved heart repair upon myocardial infarction: Combination of magnetic nanoparticles and tailored magnets strongly increases engraftment of myocytes. (February 2018) - Ottersbach, Annika; Mykhaylyk, Olga; Heidsieck, Alexandra; Eberbeck, Dietmar; Rieck, Sarah; Zimmermann, Katrin; Breitbach, Martin; Engelbrecht, Britta; Brügmann, Tobias; Hesse, Michael; Welz, Armin; Sasse, Philipp; et al.
Abstract: Cell replacement in the heart is considered a promising strategy for the treatment of post-infarct heart failure. Direct intramyocardial injection of cells proved to be the most effective application route, however, engraftment rates are very low (<5%) strongly hampering its efficacy. Herein we combine magnetic nanoparticle (MNP) loading of EGFP labeled embryonic cardiomyocytes (eCM) and embryonic stem cell-derived cardiomyocytes (ES-CM) with application of custom designed magnets to enhance their short and long-term engraftment. To optimize cellular MNP uptake and magnetic force within the infarct area, first numerical simulations and experiments were performed in vitro . All tested cell types could be loaded efficiently with SOMag5-MNP (200 pg/cell) without toxic side effects. Application of a 1.3 T magnet at 5 mm distance from the heart for 10 min enhanced engraftment of both eCM and ES-CM by approximately 7 fold at 2 weeks and 3.4 fold (eCM) at 8 weeks after treatment respectively and also strongly improved left ventricular function at all time points. As underlying mechanisms we found that application of the magnetic field prevented the initial dramatic loss of cells via the injection channel. In addition, grafted eCM displayed higher proliferation and lower apoptosis rates. Electron microscopy revealed better differentiation of engrafted eCM, formation of cell to cell contacts and more physiological matrix formation in magnet-treated grafts. These results were corroborated by gene expression data. Thus, combination of MNP-loaded cells and magnet-application strongly increases long-term engraftment of cells addressing a major shortcoming of cardiomyoplasty.